TRADISI LOKAL : RITUAL SOPIK DI TAHANE MAKEAN PULAU HALMAHERA SELATAN - Syahril Muhammad; Rustam Hasim; Jainudin Abdullah (JURNAL ILMU BUDAYA, 2022)
This study focuses on three main problems, namely (1) how the history of the "Sopik" ritual is carried out, (2) how the "Sopik" ritual is customary law and (3) how the social values ​​and cultural meanings are contained in the "Sopik" ritual. The method used in this research is qualitative. The results showed that the ritual ceremony "Sopik" in the village of Tahane, Makean island is hereditary and is a manifestation of the interaction between Islamic culture and local culture. The traditional ritual ceremony of "Sopik" in Tahane village has long historical roots and is still preserved by the community and the "Sopik" ritual was practised in the beginning, there were disputes between the community members about the village boundaries that could not be resolved. There have been many solutions taken by village leaders, but also no final decision has been reached.